2004
DOI: 10.1080/14034940310019218
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychosocial factors on the duration of breastfeeding

Abstract: To help the mothers who would like to breastfeed their baby, we must improve our ability to identify mothers at risk of early cessation. Mother's schooling, her intention, self-efficacy and earlier breastfeeding experience can be used as early predictors. An intervention should aim at improving the self-efficacy and resources of these mothers, with a focus on practical knowledge. The first five weeks, when the largest proportion of the cessations occurred, require special attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
2
16

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(187 citation statements)
references
References 18 publications
10
159
2
16
Order By: Relevance
“…6,19 Since this study found that over two-thirds of women stopped breastfeeding by six weeks and this finding has been noted in other studies, [14][15][16][17][18]31 early postpartum interventions are likely to be an important factor in improving early breastfeeding cessation. Our study highlights the most frequently cited reasons for breastfeeding cessation, how these reasons change with infant weaning age, as well as how they vary across different maternal sociodemographic groups and with maternal and newborn medical e184 REVUE CANADIENNE DE SANTÉ PUBLIQUE • VOL.…”
Section: Conclusion and Recommendationsmentioning
confidence: 78%
See 1 more Smart Citation
“…6,19 Since this study found that over two-thirds of women stopped breastfeeding by six weeks and this finding has been noted in other studies, [14][15][16][17][18]31 early postpartum interventions are likely to be an important factor in improving early breastfeeding cessation. Our study highlights the most frequently cited reasons for breastfeeding cessation, how these reasons change with infant weaning age, as well as how they vary across different maternal sociodemographic groups and with maternal and newborn medical e184 REVUE CANADIENNE DE SANTÉ PUBLIQUE • VOL.…”
Section: Conclusion and Recommendationsmentioning
confidence: 78%
“…[14][15][16][17][18] Prenatal and postpartum interventions designed to prolong breastfeeding duration may be particularly beneficial if they target this particularly vulnerable post-delivery period. We attempted to identify maternal socio- demographic and pregnancy factors associated with women who stop breastfeeding early.…”
Section: Discussionmentioning
confidence: 99%
“…Facteurs sociodémographiques et culturels Les mères plus âgées [9][10][11][12], mariées [13], primipares [8,14,15], d'un niveau de scolarité supérieur [9,10] et les femmes socioéconomiquement plus favorisées [10] allaitent plus et plus longtemps.…”
Section: Facteurs Liés à La Mèreunclassified
“…Le désir prénatal d'allaiter ou de ne pas allaiter prédit en grande partie le comportement de la mère après la naissance de l'enfant [20]. Ainsi, l'intention prénatale d'allaiter de manière prolongée est significativement associée à un allaitement prolongé [9,10,21]. Inversement, si une ambivalence est ressentie chez la mère durant la grossesse, la probabilité d'arrêter l'allaitement très tôt après la naissance est augmentée.…”
Section: Facteurs De Choix Personnel (Intentions Motivations Décisiunclassified
“…(8,9) Studies have shown that women who perceive themselves to be competent as mothers tend to breastfeed for longer than those who do not have this perception, which also encompasses how comfortable they feel in this nursing function. (10)(11)(12) The concept of maternal confidence in breastfeeding ability, theoretically conceptualized as Breastfeeding Self-efficacy (BSE), was developed based on the Cognitive Social Theory proposed by Bandura, and relates to the woman's perception of her ability to breastfeed her child; this means that mothers need to believe that they have the knowledge and skills to successfully breastfeed their children for this practice to be successful. (13) Despite these findings, maternal confidence was still little explored among adolescent mothers.…”
Section: Introductionmentioning
confidence: 99%